Geology and U–Pb geochronology of the Warlawurru Supersuite and MacDougall Formation in the Mitika and Wanarn areas, west Musgrave Province: Geological Survey of Western Australia - Quentin de Gromard, R.; Wingate, M.; Kirkland, Chris; Howard, H.; Smithies, R. (2016)
Recent field mapping and U–Pb zircon geochronology in the Mitika and Wanarn areas revealed a new basement component in the west Musgrave Province. Three samples of strongly foliated to gneissic metasyenogranite yielded U–Pb crystallization ages of c. 1607, 1593, and 1583 Ma. These rocks, assigned to the c. 1600 Ma Warlawurru Supersuite, are the oldest known crystalline rocks in the west Musgrave Province. This result is consistent with Hf isotope data, which suggest that a crust-forming event took place at 1600–1550 Ma. Metagranites of the Warlawurru Supersuite are only found within a northeast-directed thrust sheet in the Wanarn area. They are tectonically interleaved with psammitic gneisses of the MacDougall Formation, the basal unit of the Kunmarnara Group deposited within the Ngaanyatjarra Rift. Elsewhere in the Wanarn area, northwest- to west-directed thrust sheets tectonically interleave metagranites of the 1220–1150 Ma Pitjantjatjara Supersuite with the MacDougall Formation. Detrital zircon age spectra from metasedimentary rocks of the Mitika and Wanarn areas demonstrate that the large low-magnetic and low-gravity area that disrupts the otherwise high geophysical response of the Musgrave Province is dominated by the MacDougall Formation. The youngest 15 analyses in one sample yielded a mean age of 1153 ± 9 Ma, which is a maximum age for deposition of the formation. Detrital zircon ages in nine samples combined define major age components at c. 1611, 1566, and 1505 Ma, minor groups at c. 1428 and 1405 Ma, and a dominant component at c. 1179 Ma. The absence of zircons older than c. 1620 Ma precludes most of the surrounding regions as sedimentary sources to the MacDougall Formation. Good matches between detrital zircon age components and the ages of likely source regions, together with the absence of 1345–1293 Ma zircons from the west Musgrave Province, suggest that the source of MacDougall Formation detritus was the central and eastern Musgrave Province and/or basement rocks of the Madura or Coompana Provinces beneath the Eucla Basin.